A Comprehensive Analysis of Post-partum Depression Risk Factors: The Role of Socio-Demographic, Individual, Relational, and Delivery Characteristics - Smorti, Martina; Ponti, Lucia; Pancetti, Federica (Frontiers in Public Health, 2019)
Postpartum depression is a common and complex phenomenon that can cause relevant negative outcomes for children, women and families. The existing literature highlights a wide range of risk factors. The main focus of this paper is to jointly investigate different types of risk factors (socio-demographical, psychopathological, relational, and related to labor and birth experience) in post-partum depression onset in women during first-child pregnancy identifying which of these are the most important predictors. A cohort longitudinal study was conducted on 161 Italian nulliparous low risk women (Mage = 31.63; SD = 4.88) without elective cesarean. Data was collected at three different times: Socio-demographical, prenatal anxiety and depression, and quality of close relationship network (with mother, father and partner, and the prenatal attachment to child) were assessed at T1 (week 31-32 of gestation); clinical data on labor and childbirth (mode and typology of delivery, duration of labor, duration of eventual administration of epidural analgesia, and child’s APGAR index at birth) were registered at T2 (the day of childbirth); and the degree of post-natal depression symptomatology was measured at T3 (one month after birth). Postpartum depression is associated with several risk factors (woman’s age, woman’s prenatal psychopathological characteristics, the level of prenatal attachment to child, the quality of romantic relationship, and some clinical delivery difficulties). However, overall, the level of prenatal attachment to child was the most important predictor of post-partum depression. These findings emphasize the very important role of prenatal attachment for the onset of postpartum depression and the need to promote adequate and targeted prevention interventions. Limitations, strengths, and theoretical and clinical implications are discussed.